Quality of Shariah compliance assurance in Malaysian Islamic Banks posts implementation of Shariah governance framework - Mohd Haridan, Nurfarahin (2016)
Shariah board has been a great spur to the prudence of Islamic banks by ensuring Shariah compliance on the operations of Islamic banks. The aim of this study is to investigate the quality of Shariah compliance assurance from the Shariah compliance review and audit carried out in Islamic banks. In doing so, the role of Shariah boards and other internal mechanisms available to support this role have been critically evaluated. This study used a qualitative case study research design and employed semi-structured interviews to gain an in-depth understanding on the current governance practiced in Islamic banks. Analysis from interviews conducted with fourteen key individuals in two Islamic banks indicated that the quality of Shariah compliance assurance provided by Shariah board has improved. The emphasis on Shariah audit laid down in Shariah Governance Framework (SGF) has enhance the credibility of Shariah board in providing a quality Shariah assurance on the operations of Islamic bank. However, the empirical findings indicated that the Shariah compliance review roles of Shariah boards were not effectively undertaken by Shariah board as they were highly dependent on the report of Shariah Department Officer. In addition, Shariah board only participates in the development of Shariah audit plan and later endorses audit findings carried out by Shariah Audit Officers. Drawing from this heavy reliance of Shariah board on the work of Internal Shariah Officers of Islamic banks, the call for External Shariah Auditor to provide Shariah compliance assurance remains a focal point deemed more credible to the stakeholders.